Association between non‐alcoholic fatty liver disease and peripheral artery disease in patients with type 2 diabetes. Issue 10 (9th October 2017) - Zou, Yaowu; Li, Xinde; Wang, Can; Wang, Jing; Wang, Fei; Ma, Lidan; You, Wenjun; Li, Changgui
Abstract: Background: Non‐alcoholic fatty liver disease (NAFLD) is associated with the risk of coronary heart diseases; however, the relationship between NAFLD and peripheral artery disease (PAD) in patients with type 2 diabetes has not been investigated. Aim: To investigate the association between NAFLD and PAD in patients with type 2 diabetes. Methods: We carried out a cross‐sectional study on 2646 type 2 diabetes patients ≥ 40 years. All patients provided fasting blood samples and underwent a liver ultrasonography and ankle‐brachial index (ABI) test. PAD was defined as an ABI <0.9. Multiple logistic regression analyses were performed to investigate the odds ratio (OR) for PAD associated with NAFLD. Results: Our analyses showed that patients with NAFLD had a significantly higher prevalence of PAD compared with those without NAFLD (12.8% vs 7.8%). NAFLD was associated with a 75% (OR 1.75, 95% confidence interval (CI) 1.35–2.28) increased risk of PAD after adjustment for demographic factors. Addition of various metabolic risk factors as confounders attenuated the association (OR 1.49, 95% CI 1.12–2.00). Further adjustment for C‐reactive protein led the association to be marginally significant (OR 1.33, 95% CI 0.99–1.80). Analyses stratified by gender suggested the association was much stronger among women than among men. Conclusion: Type 2 diabetes patients with NAFLD had a higher prevalence of PAD, and this association was partly, but not entirely, explained by metabolic risk factors and inflammation.